2007
DOI: 10.1139/g07-077
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function, and evolution of plantO-methyltransferases

Abstract: Plant O-methyltransferases (OMTs) constitute a large family of enzymes that methylate the oxygen atom of a variety of secondary metabolites including phenylpropanoids, flavonoids, and alkaloids. O-Methylation plays a key role in lignin biosynthesis, stress tolerance, and disease resistance in plants. To gain insights into the evolution of the extraordinary diversity of plant O-methyltransferases, and to develop a framework phylogenetic tree for improved prediction of the putative function of newly identified O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
206
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(214 citation statements)
references
References 69 publications
7
206
0
1
Order By: Relevance
“…Much of the enormous diversity of specialized metabolites in plants comes from modifications or decorations of core structures by different tailing reactions such as acylation (Bontpart et al, 2015), glycosylation (Bowles et al, 2005), methylation (Lam et al, 2007), and so on (Schwab, 2003). In addition, many studies have revealed that plant specialized metabolites accumulate with tissue specificity (Schilmiller et al, 2010;McDowell et al, 2011;Kim et al, 2012;Toubiana et al, 2012;Watanabe et al, 2013;Dong et al, 2015;Wen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the enormous diversity of specialized metabolites in plants comes from modifications or decorations of core structures by different tailing reactions such as acylation (Bontpart et al, 2015), glycosylation (Bowles et al, 2005), methylation (Lam et al, 2007), and so on (Schwab, 2003). In addition, many studies have revealed that plant specialized metabolites accumulate with tissue specificity (Schilmiller et al, 2010;McDowell et al, 2011;Kim et al, 2012;Toubiana et al, 2012;Watanabe et al, 2013;Dong et al, 2015;Wen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tomato A3′5′OMT catalyzes the methylation of quercetin, myricetin, quercetin 3-glucoside, quercetin 3-rutinoside, delphinidin 3-glucoside, and cyanidin 3-glucoside, and its strong preference for delphinidin 3-glucoside was demonstrated (Roldan et al 2014). These AOMTs are closely related to the caffeoyl CoA OMT (CCoOMT) clade (Group A1) in the plant OMT family (Lam et al 2007;Provenzano et al 2014) in terms of their amino acid sequences and they are designated as CCoOMT-like proteins, together with Arabidopsis spermidine methyltransferase (Fellenberg et al 2008) and an ice plant OMT, which has a broad substrate specificity (Ibdah et al 2003).…”
mentioning
confidence: 99%
“…Plant O-methyltransferases constitute a large family made up of two major clades, A and B, consisting of two and three subgroups respectively (Lam et al, 2007). The DIFe proteins belong to the A1 subfamily (Supplemental Fig.…”
Section: Dife Genes Encode Proteins With Similarity To O-methyltransfmentioning
confidence: 99%
“…S1; Supplemental Table S2), which contains caffeoylCoenzyme A O-methyltransferases (CCoA-MTs) and an AMT from grape known as VvAOMT1 (Hugueney et al, 2009), also known as flavonol and anthocyanin O-methyltransferase (Lücker et al, 2010). Other (putative) flavonoid methyltransferases, such as the Arabidopsis flavanol 39methylase AtOMT1 (Saito et al, 2013), and enzymes with similar activities from Catharanthus roseus and Mentha 3 piperita, belong to the B1 and B2 groups (Lam et al, 2007;Supplemental Fig. S1) and are only distantly related to DIFe proteins.…”
Section: Dife Genes Encode Proteins With Similarity To O-methyltransfmentioning
confidence: 99%
See 1 more Smart Citation